Efecto antibacteriano "In vitro" del extracto etanólico de la hoja de Erythoxylum novogranatense (Coca) y la clorhexidina frente a Streptococcus mutans ATCC25175 - Castañeda León, Lesly (2017)
ABSTRACT Objective: To evaluate the in vitro antibacterial effect of the ethanolic extract of Erythroxylum novogranatense leaf and 2% chlorhexidine against Streptococcus mutans ATCC25175. Material and methods: The antibacterial effect was determined by the susceptibility test using the Kirby-Bauer method. Twenty-three replicates were performed for each treatment (ethanolic extract of the coca leaf at different concentrations and for the 2% chlorhexidine control group). Strains of Streptococcus mutans were seeded on plates containing Mueller Hinton culture medium, discs were placed with the different concentrations of ethanolic extract of the coca leaf, then the plates were incubated at 37 ° C in micro anaerobiosis, the halos being measured with A millimeter rule after 24 hours. Results: The inhibition halo averages were 8.70; 9.96; 10.96; 13.04; 24.70mm corresponding to the concentrations 10%, 25%, 50% and 75% respectively. Statistical analysis of the data revealed a highly significant statistical difference between the different groups (ANOVA: P <0.01). The average colony-forming units for the 10% concentration group were 0.04x101 and for the 25%, 50% and 75% concentration groups it was 0 UFC Conclusion: The ethanol extract of Erythroxylum novogranatense sheet and 2% chlorhexidine have antibacterial effect in vitro on the growth of Streptococcus mutans ATCC21175.